Associative effects between red clover and kikuyu grass silage: Proteolysis reduction and synergy during in vitro organic matter degradation - Guzatti G.C.* (2017)
© 2017 Elsevier B.V.The aim of this study was to evaluate the effects of the association between red clover (RC; Trifolium pratense) and a tropical grass (kikuyu grass) on the proteolysis of ensiled material and the in vitro degradation of protein and organic matter. Red clover and kikuyu grass were ensiled in the following proportions: 0:1000, 250:750, 500:500, 750:250, and 1000:0 g/kg of dry matter (DM). The fraction of rapidly degradable protein, the ammonia nitrogen (NH3-N) content of the silo, the in vitro protein degradation, and the degradation rate decreased linearly (P < 0.001) as the RC content in the ensiled material increased. Cumulative gas production after 24 h incubation showed a positive quadratic effect when RC was increased to 500 g/kg (P < 0.001). The silages with the highest RC content reduced proteolysis more effectively during ensiling and ruminal fermentation. Inter-species synergistic effects positively affected in vitro gas production, which was optimal when RC and kikuyu grass were ensiled in the same proportions as that of total DM.